Effect of capsule placement with transnasal endoscopy. Issue 2 (2nd July 2012) - Matsunaga, Takaharu; Hashimoto, Shinichi; Okamoto, Takeshi; Harima, Satoko; Tanabe, Ryo; Nishikawa, Jun; Sakaida, Isao
<x xml:space="preserve">Abstract</x> Aim: One of the prohibiting factors in achieving complete small bowel capsule endoscopy is slow gastric transit of the capsule. The present study retrospectively investigated the success rate of, and the time required for, transnasal endoscope‐assisted capsule placement to assess its clinical utility. Methods: In 24 of 27 patients who underwent capsule placement assisted by a transnasal endoscope, the capsule was successfully transported to and released in the duodenum (capsule placement group). For each patient in the capsule placement group, three age‐ and sex‐matched patients who underwent conventional capsule endoscopy were assigned as controls (n = 72). Gastric transit time, small bowel transit time, and rate of capsule arrival at the cecum within 8 h were compared between the two patient groups. Results: Among the 27 patients in whom capsule placement was carried out, the capsule was successfully placed in the duodenum in 24 patients (88.9% success rate). In the capsule placement group, gastric transit time was significantly shorter (10.5 vs 46.2 min, P = 0.0021), small bowel transit time was significantly longer (354.7 vs 301.3 min, P = 0.0134), and completion rate (capsule arrival at the cecum within 8 h) was significantly higher (83.3 vs 61.1%, P = 0.0455) than in the control group. There were no procedural accidents associated with capsule placement. Conclusion: Transnasal endoscope‐assisted capsule placement appears to be a safe and reliable procedure, achieving complete small bowel capsule endoscopy, and is considered clinically useful.